Transcatheter aortic valve implantation with balloonexpandable valve: early experience from China - Qingsheng Lu; Yifei Pei; Hong Wu; Zhinong Wang; Jing Zaiping (Brazilian Journal of Cardiovascular Surgery, 2015)
Abstract Objective: The aim of the current study was to evaluate the early experience of the application of transcatheter aortic valve implantation with the balloon-expandable system in China. The transcatheter aortic valve implantation technology has been widely used for patients with inoperable severe aortic stenosis in the developed world. The application of transcatheter aortic valve implantation is still in the early stages of testing in China, particularly for the balloon-expandable valve procedure. Methods: This was a retrospective study. All patients undergoing transcatheter aortic valve implantation with balloon-expandable system in our hospital between 2011 and 2014 were included. Edwards SAPIEN XT Transcatheter Heart Valve was used. The improvement of valve and heart function was evaluated as well as 30-day mortality and major complications according to the VARC-2 definition. Results: A total of 10 transcatheter aortic valve implantation procedures with the balloon-expandable system were performed in our hospital, of which 9 were transfemoral and 1 was transapical. The median age was 76 years, and the median STS score and Logistic EuroSCORE (%) were 8.9 and 16.2. The implantation was successfully conducted in all patients, only 2 patients had mild paravalvular leak. There was no second valve implantation. Moreover, no 30-day mortality or complications was reported. Following the transcatheter aortic valve implantation procedure, the heart and valve functions had improved significantly. During the follow-up period of 3-34 months, one patient died of lung cancer 13 months after the operation. Conclusion: This early experience has provided preliminary evidence for the safety and efficacy of transcatheter aortic valve implantation procedure with the balloon-expandable system in the developing world with an increasing aging population.